Investigating a Large-Scale Creeping Landmass Using Remote Sensing and Geophysical Techniques—The Case of Stropones, Evia, Greece - Alexopoulos, John D.; Giannopoulos, Ioannis-Konstantinos; Gkosios, Vasileios; Dilalos, Spyridon; Voulgaris, Nicholas; Serafeim E. Poulos (Geosciences, 2025)
The present paper deals with an inhabited, creeping mountainous landmass with profound surface deformation that affects the local community. The scope of the paper is to gather surficial and subsurface information in order to understand the parameters of this creeping mass, which is usually affected by several parameters, such as its geometry, subsurface water, and shear zone. Therefore, a combined aerial and surface investigation has been conducted. The aerial investigation involves UAV’s LiDAR acquisition for the terrain model and a comparison of historical aerial photographs for land use changes. The multi-technique surface investigation included resistivity (ERT) and seismic (SRT, MASW) measurements and density determination of geological formations. This combination of methods proved to be fruitful since several aspects of the landslide were clarified, such as water flow paths, the internal geological structure of the creeping mass, and its geometrical extent. The depth of the shear zone of the creeping mass is delineated at the first five to ten meters from the surface, especially from the difference in diachronic resistivity change.